Household heterogeneity in the euro area since the onset of the great recession - Miguel Ampudia; Akmaral Pavlickova; Jiri Slacalek; Edgar Vogel (European Central Bank (ECB), 2014)
We extend household-level data from the Household Finance and Consumption Survey using aggregate series and micro-simulations to investigate heterogeneity in the euro area. We quantify shocks to wealth, income and financial pressure faced by various categories of households since the onset of the Great Recession. The shocks differ substantially both across countries and across economic and socio-demographic characteristics. We find that the rising unemployment rate disproportionately affected the income-poor, while the declining wealth the income-rich. Although borrowers benefited from the substantial decrease in interest rates, debt service-income and debt-income ratios for poor households went up as they faced falling incomes. Household deleveraging was primarily driven by the restrained mortgage borrowing by the young. In several countries and at the euro-area level the unprecedented declines in asset prices substantially contributed to the sluggish consumption growth driven by both rich and poor households: while the former were hit by large shocks to wealth, the latter also significantly cut their spending because of their high MPCs.
Keywords: D12; D31; E21; 330; deleveraging; financial pressure; Great Recession; household finance and consumption survey; household heterogeneity; income; wealth; wealth effect